Are aquaculture growth policies in high-income countries due diligence or illusionary dreams? Foreseeing policy implications on seafood production in Singapore. (May 2020) - Bohnes, Florence Alexia; Rodriguez, U-Primo; Nielsen, Max; Laurent, Alexis
Highlights: Singapore announced an ambitious new policy to increase its food self-sufficiency. We investigated the potential implications of this policy for aquaculture production. An economic model with high level of technological disaggregation of supply was used. The business-as-usual scenario did not allow Singapore to fulfil its goal. The two explorative scenarios did, one of them with almost 30% decrease in imports. Abstract: In the beginning of 2019, the Singaporean government announced its desire to increase domestic food production and, in particular, aquaculture to reach 30% of self-sufficiency by 2030. Similar policies aiming at encouraging aquaculture growth abound in high-income countries in recent years, but have had limited success. Hence, this paper investigates the potential implications of such policies to foresee consequences beforehand and improve the policy's chances of success. Three scenarios of aquaculture development are built for Singapore until 2040, among which a business-as-usual scenario and two explorative scenarios aiming at increasing aquaculture production, the first emphasizing existing technologies and the second giving priority to novel and innovative ones, like recirculating aquaculture systems. These scenarios are assessed using an adapted version of the supply-demand partial equilibrium model Asiafish to challenge their viability in the socioeconomic context of Singapore. Only the two explorative scenarios are found to allow the Singaporean government to reach its goal in terms of seafood self-sufficiency by 2030, one of which appears to have strong advantages. In this scenario, imports decrease by 28% by 2040, seafood self-sufficiency reaches 69% and 90% of all aquaculture originates from innovative technologies, which would make Singapore an aquaculture tech-hub. It also has higher benefits within Singapore environmental, social and economic constraints such as land and aquafeed scarcity.